2002
DOI: 10.2519/jospt.2002.32.11.560
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal First Ray Mobility in Women Athletes With a History of Stress Fracture of the Second or Third Metatarsal

Abstract: Study Design: Retrospective case-control study. Objective: To examine the amount of dorsal first ray mobility in subjects having a history of stress fracture of the second or third metatarsal as compared to control subjects, and to test the influence of navicular drop, length of the first ray, and generalized joint laxity on the measure of dorsal mobility. Background: Instability of the first ray may cause the lesser metatarsals to carry greater weight and contribute to the incidence of metatarsal stress fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…This agreed with Glasoe et al [7] who stated that the 2 nd and 3 rd MT's had the greatest incidence of MT stress fractures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This agreed with Glasoe et al [7] who stated that the 2 nd and 3 rd MT's had the greatest incidence of MT stress fractures.…”
Section: Discussionsupporting
confidence: 90%
“…Our main focus were on the 2 nd and 3 rd MT's since they are the most common locations for MT stress fractures, and account for 75% of all MT stress fractures in sports [7]. The 2 nd MT increased in length by 0.05% and decreased in width by 10.7% showing a 40.54% increase in the stress potential (Table 1) between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…36 Metatarsal injuries and fractures are relatively common injury that may affect the foot function and performance. 41,42 The M2 and M3 are prone to stress fractures if subject has a low or collapsed longitudinal arch or other foot disabilities. These pathologies change the weight bearing of the foot because of the extreme stress loading on these metatarsals.…”
Section: Discussionmentioning
confidence: 99%
“…25 Achilles contracture has been hypothesised to increase plantar pressure, thus increasing risk of a metatarsal stress fracture. 36 Ringham et al 37 have suggested that excessive external rotation of the hip from femoral antetorsion produces foot hyperpronation, which may lead to stress fractures in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%